2016
DOI: 10.9789/2175-5361.2016.v8i3.4841-4849
|View full text |Cite
|
Sign up to set email alerts
|

Atuação do enfermeiros da Estratégia Saúde da Família na prevenção do pé diabético Practice nurse family health strategy in the prevention of diabetic foot

Abstract: Objetivos: Identificar orientações fornecidas pelos enfermeiros às pessoas com DM sobre o cuidado com os pés; investigar a frequência da realização do exame dos pés e os aspectos avaliados; verificar quais atividades de educação em saúde são realizadas pelos enfermeiros para as pessoas com DM. Métodos: estudo descritivo com abordagem quantitativa, realizado com 38 enfermeiros da Estratégia Saúde da Família, através de um questionário, durante maio a julho/2013. Os dados foram analisados com base na estatística… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
1
4
0
14
Order By: Relevance
“…Individuals having DM show involvement of the sensory, motor and autonomic fibers, reducing sweat in the feet, leaving them dry and predisposing them to cracks and fissures, which increases the risk of injury. 25 The foot cracks presence corroborated the results of a study carried out with 51 individuals having DM that showed a prevalence of 33.5%. 5 The high prevalence of cracking and dry skin indicates the need for attention during the physical examination of the feet, since these factors constitute a gateway to microorganisms and consequently can become a infection focus.…”
Section: Resultssupporting
confidence: 81%
“…Individuals having DM show involvement of the sensory, motor and autonomic fibers, reducing sweat in the feet, leaving them dry and predisposing them to cracks and fissures, which increases the risk of injury. 25 The foot cracks presence corroborated the results of a study carried out with 51 individuals having DM that showed a prevalence of 33.5%. 5 The high prevalence of cracking and dry skin indicates the need for attention during the physical examination of the feet, since these factors constitute a gateway to microorganisms and consequently can become a infection focus.…”
Section: Resultssupporting
confidence: 81%
“…Other studies that aimed to evaluate the self-care activities of adults with DM2, in which the instrument used for the evaluation was the SDSCA, found lower means (25,29) . The periodic examination of the feet allows the prevention of diabetic foot complications (30) .…”
Section: Discussionmentioning
confidence: 99%
“…12 The role of the nurse in health education is highlighted, since the training of this professional includes the knowledge and skills necessary to act in this area, integrating education activities as a form of care. 13 The reality of nursing care practice in hospitals still focused on biological and technological aspects is also an issue in our daily lives. In general, nurses are engaged in functions that are divided between the demands of the assistance directed to technical procedures and management, finding little time for the development of health education activities.…”
Section: Introductionmentioning
confidence: 99%